Diversity and importance of the Cucurbitaceae family in Mexico - Lira, Rafael; Rodriguez-Jimenez, Concepcion; Alvarado, José L.; Rodriguez, Isela; Castrejon, Javier; Dominguez-Marian, Antonio (Instituto de Ecología, A.C., 1998)
In this paper a general overview of the taxonomic and floristic knowledge of the family Cucurbitaceae in Mexico is presented. The family is represented in this country by 137 taxa (species and infraspecific categories), belonging to 38 genera of its two subfamilies (Zanonioideae and Cucurbitoideae). Thirteen of the taxa are mainly crops for human consumption, the rest growing wild, of which more tan 50% are endemic to relatively small áreas of the country. Some of the wild taxa are closely related to crops of worldwide importance, and several are used mainly in folk medicine in various regions of the country.